A higher volume of fibrotic tissue on virtual histology prior to coronary stent implantation predisposes to more pronounced neointima proliferation. Issue 2 (4th March 2018) - Haine, Steven; Wouters, Kristien; Miljoen, Hielko; Vandendriessche, Tom; Claeys, Marc; Bosmans, Johan; Vrints, Christiaan
Abstract: Background: Since neointima smooth muscle cells (SMC) mainly originate from the vessel wall, we investigated whether atherosclerotic plaque composition influences subsequent in-stent neointima proliferation and restenosis. Methods: We performed intravascular ultrasound (IVUS) with virtual histology in 98 patients prior to elective bare-metal stent (BMS) implantation in de novo coronary artery lesions. Virtual histology variables pre-percutaneous coronary intervention (PCI) were related to in-stent neointima proliferation six months after implantation assessed as late luminal loss of 0.88 mm (interquartile range (IQR) 0.37–1.23 mm) on angiography and as maximal percentage area stenosis of 42% (IQR 33–59%) and percentage volume intima hyperplasia of 27% (IQR 20–36%) on IVUS. A ridge-trace based multiple linear regression model was constructed to account for multicollinearity of the virtual histology variables and was corrected for implanted stent length (18 mm, IQR 15–23 mm), stent diameter (3.0 mm, IQR 2.75–3.5 mm) and lesion volume (146 mm³, IQR 80–201 mm³) prior to PCI. Results: Fibrous tissue volume prior to PCI (49 mm³, IQR 30–77 mm³) was significantly and independently related to late luminal loss ( p  = .038), maximal percentage area stenosis ( p  = .041) and percentage volume intima hyperplasia ( p  = .004). Neither absolute nor relative amounts of fibrofatty, calcified or necrotic core tissue appeared related to any of the restenosis parameters. Subgroup analysis after exclusion of acute coronary syndrome (ACS) patients yielded similar results. Conclusion: Lesions with more voluminous fibrotic tissue pre-PCI show more pronounced in-stent neointima proliferation, even after correction for lesion plaque volume.